Predictive validation of the repeated low-dose reserpine rodent model of parkinsonism - Vinicius Bioni; Alvaro C. Lima; Debora M. G. Cunha; Narriman Gonçalves; Leonardo B. Lopes-Silva; João P. Kurita; Manuela B. L. Soares; Marcela Becegato; Aline C. Ramos; Anderson H. F. F. Leão; Regina H. Silva (Experimental Brain Research, 2026)
L-DOPA (LD) is the gold-standard treatment of motor symptoms in Parkinson’s disease (PD), conventionally used to prove the predictive value of PD animal models. This study aimed to investigate the predictive validity of an adaptation of the conventional reserpine model of PD: the repeated low-dose reserpine administration in rodents, which promotes progressive motor impairment in catalepsy, vacuous chewing behavior tests, and neurochemical deficits. Specifically, we investigated the effects of acute and chronic treatment with LD on motor alterations induced in mice by this modified protocol. Swiss mice were treated with 20 reserpine injections (0.1 mg/kg, s.c., every other day). Acute LD (25, 50, 100, and 200 mg/kg) administration was performed at the end of reserpine protocol to assess immediate motor recovery. Additionally, concomitant chronic LD (50 and 100 mg/kg) treatment was conducted to investigate potential attenuation of motor impairment and dopamine depletion quantified by HPLC. Repeated reserpine protocol induced motor deficits in catalepsy and vacuous chewing evaluations and striatal dopamine depletion. Acute LD administration significantly improved catalepsy in higher doses, while chronic LD treatment attenuated motor impairments and reduced dopamine depletion in the striatum. These findings support the predictive validity of the reserpine rodent model for studying parkinsonism. Together with the ability to promote chronic and progressive parkinsonian alterations, the reversion of these deficits by LD reinforces the potential of the repeated low-dose reserpine protocol for studies of potential therapies and the pathophysiology underlying neurodegenerative processes in PD.